Pomiędzy Ukrainą a Polską: działalność społeczna i polityczna hrabiego M. Tyszkiewicza (1857-1930) - Krasiwski, Orest (Studia Europaea Gnesnensia, 2020)
This paper analyzes political activities of Count M. Tyszkiewicz. The author sets out from an overview of his descent, academic education, and family relationship. Particular attention is devoted to Tyszkiewicz’s involvement in political affairs, formation of his views, as well as social and political undertakings. Another element highlighted here is Tyszkiewicz’s activity as a patron, his contribution to the development of Ukrainian and Polish culture, and relations with Ukrainian politicians and writers at the turn of the 20th century. Furthermore, the author discusses his diplomatic achievement as a representative of Ukraine to the Holy See and the peace conference in Paris. Based on a study of correspondence between Tyszkiewicz and Ukrainian politicians, the author emphasizes his commitment to the Ukrainian cause on the international scene and efforts to seek recognition of the Ukrainian state.